Investigating tooth morbidity risks, prevalence, and interventions in tribal setting: a study protocol focused on the Irula community in Tamil Nadu - Alocious Sukumar, Margret Beaula; Peter, Roshni Mary; Joseph, Alex (Frontiers in Dental Medicine, 2024)
Dentistry is uniquely positioned as a healthcare profession, distinguished from allied health or paramedical fields. It operates within a university-based structure, maintaining primary care responsibilities. Oral diseases impose a substantial worldwide health and economic burden, profoundly affecting the well-being of those affected. This cross-sectional study is centered on the Irula tribes in Tamil Nadu, India. Investigating the extent of tooth morbidity and loss, identifying possible risk factors, looking at oral hygiene habits, and evaluating the oral health-associated quality of life (OHRQoL) in this population are the main goals. As this population is at high risk for dental issues, promoting good oral hygiene becomes crucial.Indigenous populations, including the Irula tribes, have been underrepresented in research studies. The vulnerability of the Irula tribes is exacerbated by their remote locations, resulting in limited access to fundamental healthcare facilities.This study employs a cluster sampling approach, aiming to include 880 individuals aged 60 and above from Kancheepuram and Chengalpattu districts. The methodology encompasses a community-based questionnaire, clinical assessments utilizing standardized indices, and the assessment of the Oral Health-Related Quality of Life (OHRQoL). The Statistical Package for Social Services, version 20, will be used to analyze all of the data that has been gathered (SPSS).Categorical variables will undergo analysis, with descriptive statistics and frequency percentages computed. CONCLUSION: This study evaluates tooth morbidity and dentistry's role in screening chronic diseases like diabetes among the Irula tribes. It explores risk factors, oral hygiene practices, treatment seeking behavior, and oral health-related quality of life to gain a comprehensive understanding.